THE OPPORTUNITIES FOR SUSTAINABLE CONSUMPTION AND PRODUCTION IN CENTRAL SULAWESI - mustamin mustamin; Tenripada Tenripada; Andi Mattulada; Abdul Kahar (Citakonsultindo, 2023)
This article discusses about the opportunities for sustainable consumption and production in Central Sulawesi. Where Sustainable Consumption and Production (SCP) or sustainable consumption and production as part of the Sustainable Development Goals (SDG's), is basically an effort to realize environmentally friendly and sustainable consumption and production activities by all stakeholders globally, with integrated and systematic changes from the previous pattern which is not environmentally friendly and unsustainable. The method of this article is descriptive analysis. The results of the analysis show that Central Sulawesi Province has four sectors that have the opportunity to increase the economy, namely the forestry sector, agriculture and plantations, fisheries and industry. However, the main concern is the impact of consumption and production activities in each sector on a sustainable basis. To realize the achievement of SDG's 12 goals, the authors argue that all parties must be actively involved, especially the government as a policy maker to synergize with the community so that economic and ecological sustainability can be realized through responsible consumption and production patterns .